Os destinos do desmame de executivos - demissão: um estudo sobre separação e exclusão do mundo corporativo - Giuliese, Mariá Aparecida de Barros Freire (2008)
The author uses the civilization, as well as nowadays uneasiness, as a starting point to write on the uneasiness experienced in the corporations, taking into consideration, and as a reference, the processes of dismissal-separation that happen to the executives under her care. The objective of the present study is to analyze the symbolic representation of the weaning and its destinies when the rupture with the professional activity caused by dismissal or compulsory retirement takes place. The symptoms that make clear the nature of the relation of the executives with the work, as well as the pathogenic character of the corporations have increased importance in this process. The six clinic cases presented show that the way dismissal process occurs can cause disorganization, denial of reality, resentment, resignation or relief; and clearly show that the lack of work, after dismissal or retirement, besides compromising self-image and excluding the individual from the place and position he had in the culture, it promotes anxiety and depression that may require professional care. The listening process carried out by the author is precise, and occurs only when required, with the objective of creating conditions for the executive to recognize the dismissal, work out the grief and build a new project; its purpose is to recover interests and vocations, to identify old professional projects, as well as to draw the future; and guide the executive to adequate and efficiently approach the market